Inhibitory effect of unsaturated fatty acids on lymphocyte-antigen interaction with special reference to multiple sclerosis - Field, E J; Shenton, B K (Acta neurologica Scandinavica, 1975)
Using the macrophage electrophoretic mobility (MEM) test, the in vitro effects of oleic, linoleic and arachidonic acid, as well as Naudicell oil and methyl gamma-linolenate, on lymphocyte response to various antigens (PPD, thyroid antigen and EF) were studied in patients with mutiple sclerosis, patients with other neurological diseases, and in normal subjects. In all three groups, linoleic and arachidonic acid showed a significant inhibition; the latter was greater than the former, when tested at physiological concentrations, suggesting that unsaturated fatty acids may exert an immunoregulatory effect in vivo. The methylester of gamma-linolenate is the most powerful suppressing agent yet tested. The inhibitory activity of linoleic and arachidonic acids was consistently greater in MS than in other subjects and forms the basis of an in vitro test for the disease. The possible relationship of these findings to widespread alterations in the fatty acid composition of the tissues and to the pathogenesis of MS is discussed.